PENDIDIKAN IBADAH PERSPEKTIF AL-QURAN DAN HADITS - Sudarsono (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2018)
Al-Quran is the revelation of Allah S.W.T which was revealed to the Prophet Muhammad as a guide for the whole life of mankind, not only Muslims in particular. For this reason, the Koran is an oasis in human life that is used as a guide in life. The originality of the Koran as a holy book is very guaranteed unlike other books, which until now have not been authentic and original, due to human behavior that dares to change and distort and there is no guarantee of originality certainty. Whereas in the Koran and the Hadith of the Prophet discuss the issue of Immortality or servitude to God is one of the responsibilities of man and Jin, naturally created by Allah. So that all the dynamics of human life on earth should be based on ubudiyah principles and values, both activities that are political, educational, economic, social, and so on. According to Imam al-Tabari in his interpretation; that the purpose of Allah creating man and jinn is to serve Him, if they do good they will be rewarded with reward, but if they do bad, then they will be rewarded with punishment later on the Day of Judgment. This, is not based on the needs of God, humans worship, but for the sake of benefit and the benefits also return to humans themselves.